“I Said What I Said”—Black Women and Argumentative Politeness Norms - Henning, Tempest M. (Informal Logic, 2021)
This paper seeks to complicate two primary norms within argumentation theory: 1) engaging with one’s interlocutors in a ‘pleasant’ tone and 2) speaking directly to one’s target audience/interlocutor. Moreover, I urge argumentation theorists to explore various cultures’ argumentative norms and practices when attempting to formulate more universal theories regarding argumentation. Ultimately, I aim to show that the two previously mentioned norms within argumentation obscure and misrepresent many argumentative practices within African American Vernacular English—or Ebonics, specifically the art of signifying.